Incidence of suspected human rabies virus exposure and associated risk factors in Ethiopia: systematic review and meta-analysis - Mengistie Kassahun Tariku; Abebe Habtamu Belete; Daniel Tarekegn Worede; Sewnet Wongiel Misikir (BMC Infectious Diseases)
Abstract Background Despite the World Health Organization’s 2030 goal of zero deaths, rabies disproportionately affects Asia and Africa, causing 55,000 deaths and 8.6 billion monetary losses annually. In Ethiopia, dogs are the primary cause of human rabies virus exposure due to their close interaction with humans and other domestic animals. The results of previous studies on the incidence of suspected human rabies virus exposure were inconsistent and inadequate. This study aimed to measure the pooled incidence of suspected human rabies virus exposure and associated risk factors in Ethiopia. Methods Published articles without publication date/year restriction were investigated using the guideline Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We searched PubMed, EMBASE, Science Direct, Google Scholar, and African Journals Online databases. Two independent authors extracted the required data. This meta-analysis was carried out using the program Stata Version 17, the DerSimonian-Laird method, and a random-effects model. The I2 and Cochrane Q test statistics were used to determine the studies’ heterogeneity. Egger’s test and funnel plots were used to assess publication bias. Data were displayed using forest plots of incidence and risk ratio (RR) with a 95% confidence interval. Results Eight articles with 18 data points and 116,484 sample sizes were included. The pooled incidence rate was 54.03 (95% CI: 43.92–64.13) per 100,000 population. The highest, 107.32 (95% CI: 80.20-134.45) per 100,000 population, and the lowest, 4.49 (95% CI: 2.00-6.97) per 100,000 incidence rate, were observed in the Oromia and Amhara regions, respectively. Sex was significantly associated with the incidence of human rabies exposure. Being male was (RR = 1.67, 95% CI; 1.53–1.81) times more likely to be exposed to the human rabies virus than those who were females. Conclusion The estimated incidence was found to vary by location and was reported as high. One important contributing factor was sex. Human rabies virus exposure prevention, such as dog vaccination, public awareness, and an epidemiological surveillance system, should be improved.